Sony targets laptop consumers in China : segment global or local? - Grayson, Kent, (SAGE knowledge. Cases., 2016)
The manager of the Sony VAIO personal computer in China has been given two segmentation studies. One study is country-specific and product-specific. The other is a global segmentation study, which covers all regions and all of Sony's many consumer electronics. Which segmentation study should the manager rely on - or is there a way to rely on both? After deciding which study is best, which consumer should the manager target, and with what position?